The Analysis of the Structure, Behavior, and Performance of Tual Sagu Market in Kepulauan Meranti District - Fariz Al Azmi; Syaiful Hadi; Novia Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
This study is aimed at analyzing the 1) structure; 2) behavior; and 3) performance of TualSagu market in Kepulauan Meranti Regency. This research was conducted using a survey method. Participants were selected using purposive sampling (27 farmers, 6 collectors, and 6 factory owners). The analysis of Tual Sagu market was done using descriptive, qualitative and quantitative methods. The findings show that 1) the structure of Tual Sagu market in Kepulauan Meranti Regency leads to a perfect competition market; 2) the market behavior shows an imperfect competition market leading to oligopsonism; and 3) the performance of Tual Sagu market in Kepulauan Meranti Regency is not yet efficient. This is seen from the fact that the margin marketing is greater at the merchant level and the inequality of the benefits obtained.